Kebijakan Hukum Nasional dalam Mengatasi Eksploitasi Anak di Bidang Perdagangan dan Jasa - NI MADE ANGGIA PARAMESTHI FAJAR; Fanny Priscyllia (Jurnal Yustitia, 2025)
Child exploitation in trade and services remains a serious problem in Indonesia. This study analyzes the effectiveness of national legal policies in protecting children from economic exploitation, with a focus on the implementation of Law No. 35 of 2014 on Child Protection and related legal instruments. The research method employs a normative-juridical approach through literature review and case analysis. The results indicate that although the legal framework is adequate, field implementation still faces challenges such as weak inter-institutional coordination, low public awareness, and budget constraints. This article recommends strengthening the child protection system through central-regional policy integration, capacity building for law enforcement, and restorative approaches